Access of the Public to Environmental Information in the Republic of Kazakhstan - YEREZHEPKYZY, Roza; TYNYBEKOV, Serikkali; ABIKENOV, Arkhat; ALDASHEV, Sarsengali (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017DO - 10.14505/jarle.v8.7(29).28, 2017)
In the present work, a comprehensive legal analysis of public access to information in the field of environmental protection and the use of natural resources in the Republic of Kazakhstan has been conducted, and the legal basis for securing, implementing and protecting the public's right to access to environmental information has been examined. Particular attention is paid to the problems of direct implementation of environmental information provision, as well as to the role of the public in participation in decision-making in the Republic of Kazakhstan, legal problems of judicial protection of legitimate rights and interests of the public and citizens in this field. The theoretical conclusions and recommendations on improving the legislation are substantiated, based on the requirements for the implementation of the norms of the Convention on Access to Information, Public Participation in Decision-making and Access to Justice in Environmental Matters in National Legislation.